E-GOVQUAL TESTING TECHNIQUE ON THE QUALITY OF SERVICE OF ONLINE RESIDENCE PERMIT REGISTRATION APPLICATION (APITO) AT NGURAH RAI IMMIGRATION OFFICE - Rasona S Akbar; G Gunawan; Putu Maha Permana Aditya (TEMATICS: Technology ManagemenT and Informatics Research Journals, 2021)
The implementation of the new normal carried out by the government is a sign of the reopening of immigration residence permit services in the new normal order. With the opening of the residence permit service again, it will result in queues at immigration offices in the pandemic period. Overcoming this, therefore the Immigration Office (Class I Special) Ngurah Rai utilization of information technology through a website-based application called Online Residence Permit Registration Application (APITO). This research aims to find out about the general picture of APITO and measure the quality of APITO services. The research method used in this study is a quantitative method with Electronic Government Quality (E-Govqual) testing technique that is seen from the comparison of gap between perception values and apito user expectation values. The results of this study show that APITO aims to make it easier for applicants to get a scheduled arrival to the Immigration Office and make it easier for employees to control the number of applicants to be served. In addition, apito service quality is said to be quality on community support indicators (citizen support) with an average gap analysis value of 0,08, while it is said to be less quality on efficiency indicators with an average gap analysis value of -0,50, trust (trust) average gap analysis value of -0,09, and reliability (reliability) average gap analysis value of 0,16.